1993
DOI: 10.1128/aem.59.11.3674-3680.1993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Giardia lamblia and Giardia muris cyst inactivation by ozone

Abstract: Inactivation of Giardia lamblia and Giardia muris cysts was compared by using an ozone demand-free 0.05 M phosphate buffer in bench-scale batch reactors at 22°C. Ozone was added to each trial from a concentrated stock solution for contact times of 2 and 5 min. The viability of the control and treated cysts was evaluated by using the C3H/HeN mouse and Mongolian gerbil models for G. muris and G. lamblia, respectively. The resistance of G. lamblia to ozone was not significantly different from that of G. muris und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
7

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 30 publications
1
31
0
7
Order By: Relevance
“…A plot of conc P 2 Xtime P 3 against fa or log R will give a single curve from which combinations of time and concentration can be found that will ensure a given level of disinfection. This is, essentially, what the original Ct concept was designed to do (see Finch et al 1993 for a useful discussion of the Ct method).…”
Section: The Ct Conceptmentioning
confidence: 90%
See 1 more Smart Citation
“…A plot of conc P 2 Xtime P 3 against fa or log R will give a single curve from which combinations of time and concentration can be found that will ensure a given level of disinfection. This is, essentially, what the original Ct concept was designed to do (see Finch et al 1993 for a useful discussion of the Ct method).…”
Section: The Ct Conceptmentioning
confidence: 90%
“…Microbiology has so often been seen as a purely descriptive science, and this belies the voluminous work done in mathematical biology applied to the food, home and personal care, and pharmaceutical industries. The`Ct' concept, obtained from disinfection rates, is used to set disinfection times against, for example, Giardia cysts (Baumann and Ludwig 1962;Wickramanayake et al 1985;Finch et al 1993). The rationale behind the canning process is based on thermal disinfection modelling, albeit it on a less than precise model (Anderson et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As for C~ptosporidium, sand filtration (Rose et al, 1989) (1988) currently appears to be the most effective technique for removing cysts from water. Ozone has been shown to have cysticidal properties in laboratory studies (Finch et al, 1993b) and hence may be of use although more data is required on the effect of factors such as treatment temperatures and water quality before an accurate picture of its reliability and feasibility in water treatment plants is achieved.…”
Section: Giardiamentioning
confidence: 99%
“…Ozone has inhibitory effects on a variety of micro-organisms (Turner et al 2000), including Staphylococcus aureus (Burleson et al 1975), Escherichia coli (Burleson et al 1975), Vibrio cholerae (Burleson et al 1975), poliovirus (Finch and Fairbairn 1991), rotavirus (Vaughn et al 1987), hepatitis A virus (Vaughn et al 1990), human immunodeficiency virus (Wells et al 1991), Aspergillus spp. (Beuchat et al 1999), Giardia lamblia and G. muris (Finch et al 1993a), Cryptosporidium parvum (Finch et al 1993b) and pathogenic amoebae (Cursons et al 1980). The effect of ozone on chlamydiae has not been determined.…”
Section: Introductionmentioning
confidence: 99%